The Effectiveness of Stocking Density on the Growth Rate and Survival Channa striata in Aquaponic Systems - Rizal Akbar Hutagalung; Suparmin Suparmin; Agus Setiawan; Farid Mudlofar; Muhammad Taufiq (Journal of Aquaculture Development and Environment, 2019)
Channa striata is the one of the local comodity in West Kalimantan Province which has important economic value. The demand for Channa striata comes mostly from urban communities, while urban areas only have narrow land / yard. One of the techniques of fish cultivation in narrow land is the aquaponics system. Thus, Channa striata cultivation with the aquaponics system can increase the productivity of cork fish in urban areas. The purpose of this study was to obtain the optimal amount of stocking density in Channa striata culture with an aquaponics system with indicators of success namely survival and growth rate. This study lasted for 75 days, taking place at the Pontianak City Fish Agribusiness Farm. The study design used a Completely Randomized Design (CRD) with 4 treatments and 3 repetitions, The stocking solid treatment used in this study is A: 40, B: 60, C: 70, and D: 50 tails / m2. The results showed that treatment A had a significant effect on the absolute growth rate of 12.85 gr followed by perlkuan D: 12.46 gr, B: 8.87 gr, C: 7.9 gr, while the best specific growth rate was needed at time A: 3.50%, D: 3.44%, B: 3.05%, C: 2.91%. The observation of life survival also has the same trend, namely the best treatment in treatment A: 95%, D: 90%, B: 70%, C: 49%. From the results of these studies it can be concluded that the higher the stocking density in aquaponics fish farming systems will have an impact on the growth rate and the survival rate of Channa striata with the best treatment, namely with stocking density of 40 fish / m2.